INNV-27. AN INNOVATIVE VIRTUAL MULTI-INSTITUTIONAL, MULTIDISCIPLINARY NEURO-ONCOLOGY TUMOR BOARD: THE NIH-NOB EXPERIENCE DURING THE COVID-19 PANDEMIC. (12th November 2021) - Rogers, James; Acquaye, Alvina; Ikiddeh-Barnes, Ukeme; Benson, Kaitlyn; Boris, Lisa; Akindona, Funto; Frederico, Stephen; Jammula, Varna; Kim, Yeonju; Timmer, Michael; Aboud, Orwa; Avgeropoulos, Nicholas; et al.
Abstract: BACKGROUND: The American Academy of Neurology Institute and Society for Neuro-Oncology recommend multidisciplinary tumor board (MTB) meetings as a quality metric in neuro-oncology. With the COVID-19 pandemic resulting in travel restrictions, we expanded our existing MTB by transitioning to a virtual format that maintained our commitment to providing consultation for primary CNS tumor cases. This transition permitted participation by neuro-oncology teams from over 30 Brain Tumor Trials Collaborative (BTTC)/National Cancer Institute-Comprehensive Oncology Network Evaluating Rare CNS Tumors (NCI-CONNECT) centers across the United States. Here, we describe results from opening our MTB remotely to these teams. METHODS: We retrospectively reviewed records from remote MTB meetings held between April 2020 and March 2021. To gauge the impact of our MTB on clinical management, we administered a brief survey querying BTTC members. RESULTS: Twenty-eight providers presented 41 cases during 24 virtual MTB meetings (range: 1-4 cases per meeting). Two cases (5%) were presented only for educational value. Approximately half (54%) of the cases discussed dealt with diagnosis/management of an NCI-CONNECT rare CNS tumor. During MTB discussions of the 39 cases seeking diagnosis/management recommendations, 32% received clinical trial recommendations, 10% were suggested to enroll in the NCI Neuro-Oncology Branch (NOB) Natural History Study (NCT02851706), 17% received a recommendation to obtain central neuropathology review, and 100% received recommendations for further disease management. Most BTTC survey respondents (83%) found these recommendations impactful in the management/treatment of their presented case or generally useful/informative for their clinical practice. CONCLUSION: We describe the feasibility and utility of an innovative virtual multi-institutional MTB. These novel remote meetings allowed for discussion of complex neuro-oncology cases and recommendations from experts, particularly important for those with rare CNS tumors. Our study's findings during the COVID-19 pandemic of the value of providing remote access to MTBs should apply post-pandemic.